Proteomic Analysis of Aorta and Protective Effects of Grape Seed Procyanidin B2 in db/db Mice Reveal a Critical Role of Milk Fat Globule Epidermal Growth Factor-8 in Diabetic Arterial Damage - Yu, Fei (Public Library of Science, 2012)
BACKGROUND: Atherosclerosis is one of the major complications of type 2 diabetic patients (T2DM), leading to morbidity and mortality. Grape seed procyanidin B2 (GSPB2) has demonstrated protective effect against atherosclerosis, which is believed to be, at least in part, a result of its antioxidative effects. The aim of this study is to identify the target protein of GSPB2 responsible for the protective effect against atherosclerosis in patients with DM. METHODS AND RESULTS: GSPB2 (30 mg/kg body weight/day) were administrated to db/db mice for 10 weeks. Proteomics of the aorta extracts by iTRAQ analysis was obtained from db/db mice. The results showed that expression of 557 proteins were either up- or down-regulated in the aorta of diabetic mice. Among those proteins, 139 proteins were normalized by GSPB2 to the levels comparable to those in control mice. Among the proteins regulated by GSPB2, the milk fat globule epidermal growth factor-8 (MFG-E8) was found to be increased in serum level in T2DM patients; the serum level of MFG-E8 was positively correlated with carotid-femoral pulse wave velocity (CF-PWV). Inhibition of MFG-E8 by RNA interference significantly suppressed whereas exogenous recombinant MFG-E8 administration exacerbated atherogenesis the db/db mice. To gain more insights into the mechanism of action of MFG-E8, we investigated the effects of MFG-E8 on the signal pathway involving the extracellular signal-regulated kinase (ERK) and monocyte chemoattractant protein-1 (MCP-1). Treatment with recombinant MFG-E8 led to increased whereas inhibition of MFG-E8 to decreased expression of MCP-1 and phosphorylation of ERK1/2. CONCLUSION: Our data suggests that MFG-E8 plays an important role in atherogenesis in diabetes through both ERK and MCP-1 signaling pathways. GSPB2, a well-studied antioxidant, significantly inhibited the arterial wall changes favoring atherogenesis in db/db mice by down-regulating MFG-E8 expression in aorta and its serum level. Measuring MFG-E8 serum level could be a useful clinical surrogate prognosticating atherogenesis in DM patients.